THU0628 Patterns of etanercept dose adjustments in a real–world setting: a canadian retrospective cohort study. (15th June 2017) - Khraishi, M; Zhang, Y; Ivanovic, J; Millson, B; Singh, E; Woolcott, J; Jones, H
Abstract : Background: Etanercept is a soluble TNF receptor (humanized protein) indicated for treatment of immune-mediated inflammatory diseases, including rheumatoid arthritis (RA), psoriatic arthritis (PsA), psoriasis (PsO), and ankylosing spondylitis (AS). Canadian monograph recommended dosing of etanercept is 50mg/week, with select indications also requiring an initial loading phase of 100mg/week for 12 weeks. Evidence suggests that real-world practices differ from monograph, with patients titrating to lower or higher weekly dosing as needed. Limited research exists on how etanercept patients are dose optimized in the real-world Canadian setting. Objectives: To describe etanercept treatment dynamics, including dose de-escalation/escalation in the Canadian real-world setting. Methods: A retrospective cohort study was conducted utilizing claims-level data from QuintilesIMS Private Drug Plan database, Ontario Public Drug Plan database, and Quebec Public Drug Plan database. Between 07/2013–06/2015, bio-naïve patients who initiated etanercept and who retained on therapy for 12 months were identified. Weekly dosing of each patient was calculated and analyzed for the prevalence and magnitude of dose de-escalation/escalation. Patients with at least 20% lower/higher average dose than monograph recommended dose (50mg/week) were flagged as dose de-escalators/dose escalators, respectively. The first 3 claims of etanercept were excluded from average dose calculations to exclude a possible loading phase. Results: The study identified 3, 051 etanercept patients (60% female, 77% aged between 18 and 65, 87% rheumatic diseases, and 13% PsO) across Canada in the selection period. Overall, 11% (n=332) of patients de-escalated during their first year of therapy, led by AS (15%, n=24) and RA (12%, n=286); 15% (n=449) of patients escalated, led by PsO (64%, n=262) versus 7% (n=168) in RA; 74% (n=2, 270) of patients maintained a consistent dose. Average dosing across rheumatic disease patients stabilized to monograph levels by week 20 of their therapy; PsO patients' dosing was observed to be lower than monograph during the loading phase, while higher than monograph in the maintenance phase. Conclusions: In Canadian real-world practice, the average patient utilization of etanercept remained consistent over the first year in majority of patients, with the exception of those with PsO. A notable proportion of etanercept patients with rheumatic diseases reduced their average dosing over time while on therapy, with almost twice as many patients titrating their dose downwards than upwards. However, in PsO patients, a majority of patients increased their etanercept. Disclosure of Interest: M. Khraishi Consultant for: Pfizer Canada and Amgen Canada, Y. Zhang: None declared, J. Ivanovic: None declared, B. Millson: None declared, E. Singh: None declared, J. Woolcott: None declared, H. Jones: None declared